Bacterial coinfections with coronavirus disease 2019 (COVID-19) - Glen Huang; Daisuke Furukawa; Bryant D. Yang; Brian J. Kim; Arthur C. Jeng (Cambridge University Press, 2021)
Abstract Background: The pandemic caused by severe acute respiratory coronavirus virus 2 (SARS-CoV-2) has dramatically increased cheshospitalizations, and it is often difficult to determine whether there is a bacterial or fungal coinfection at time of presentation. In this study, we sought to determine the rates of coinfection and utilization of antibiotics in SARS-CoV-2 disease. Methods: Retrospective chart review of patients hospitalized with COVID-19 pneumonia from April 13, 2020, to July 14, 2020. Results: In total, 277 patients were hospitalized for COVID-19 pneumonia during this period. Patients that received antibiotics within 48 hours of presentation were more likely to be febrile (59.3% vs 41.2%; P = .01) and to have leukocytosis (23.9% vs 5.9%; P < .01) and were less likely to have a procalcitonin level <0.25 ng/mL (58.8% vs 74.5%; P = .04). In total, 45 patients had positive blood cultures collected during hospitalization, 16 of which were clinically significant. Of the clinically significant blood cultures, 5 were collected <48 hours of admission. Moreover, 18 sputum cultures were clinically significant, 2 of which were collected within 48 hours of admission. Conclusion: Bacterial and fungal coinfections in COVID-19 appear to be rare on presentation; thus, this factor may be a good target for enhanced antibiotic stewardship.